Complex Stenoses and CT Features of the Nasolacrimal Canal in Congenital Nasolacrimal Duct Obstruction. Issue 6 (November 2019) - Fayet, Bruno; Racy, Emmanuel; Bordonné, Corinne; Katowitz, James A.; Katowitz, William R.; Brémond-Gignac, Dominique
Abstract : Purpose: To study the CT appearance of the nasolacrimal canal (NLC) in cases of congenital nasolacrimal duct obstruction (CNLDO) where there is a tactile sensation of a hard contact (HC) stop in the duct preventing stent intubation. Methods: The authors retrospectively reviewed all consecutive cases of chronic CNLDO observed between 2003 and 2018 in which an apparent HC obstruction prevented nasolacrimal intubation. CT scans were reviewed to determine the cause of probing failure: distal stenosis, loss of parallelism of the NLC walls, abnormal angulations or an adjacent obstacle blocking tear outflow. Results: Nine patients (12 sides) met the following criteria: CNLDO + HC + probing failure. The mean age at the time of the first HC was 3.9 years (range: 0.8–8.1 years) and at the time of a second confirmation of HC with subsequent dacryocystorhinostomy was 7.8 years (range: 4.1–9.2 years). Nasolacrimal duct opacification was noted in 33% of cases (4/12). Abnormalities of the NLC occurred in 8 of the 12 cases of CNLDO (8/12 = 66.6%) and on the asymptomatic side in 1 case (1/6 = 16.6%). A canine tooth bud situated in the same plane as the NLC was observed in 9 cases of CNLDO (9/12 = 75%) and on the asymptomatic side in 2 cases (2/6 = 33.3%). Conclusions: HC noted during probing is a sensitive but relatively nonspecific sign which, nevertheless, does indicate either a complex obstruction or at least potential intubation difficulties. As confirmed by CT imaging, a significant anatomical variant is not necessarily predictive of epiphora, but nevertheless may complicate the intubation procedure. The authors describe hard contact palpation during probing for CLNDO and its relationship to anatomic location and etiologies of obstruction in the nasolacrimal canal by CT imaging.